Change-making in a (post)apartheid city: An auto-ethnographical essay - Beer, Stephan F. de (HTS teologiese studies, 2018)
We reflect on living and doing ministry in a (post)apartheid South African city, negotiating ongoing demographic and sociopolitical transitions and discerning appropriate faith responses. We speak about the inevitability of these transitions, but then suggest that a view of theology and ministry as change-making is not inevitable but a vocation and art to be acknowledged, embraced and fostered. We argue for an epistemology from below or within, drawing from Parker Palmer’s notion of knowing as loving – in community – and reflecting on his idea that ‘to know’ is ‘to be known’. In stressing the importance of reading the city, we show how reading the city means to be read by the city too. It is in the journeys of ongoing self-awareness, and personal confrontation, change and conversion – in relation to issues of gender, race, location and class – that transformational urban imaginaries can be birthed. Finally, we reflect on urban change-making as a process of personal, communal, institutional and systemic transformation, happening on many different levels at the same time, through creating conditions and spaces for change to occur. It is an ongoing call for deepening our journeys in response to the overwhelming groans, of humanity and creation alike, for Gods’ urban shalom.